2017
DOI: 10.1021/acs.jpcb.7b03200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Interlayer Expansion of a Layered Silicate Driven by Caffeine Intercalation in the Water Phase Using Transmission X-ray Diffraction

Abstract: The kinetics of caffeine uptake into the interlayer nanospace of silicate nanosheets modified with benzylammonium (BA) was evaluated by in situ monitoring the basal spacing in aqueous media using transmission X-ray diffraction. An interlayer spacing of 0.58 nm in water before caffeine uptake indicates a monomolecular layer of BA and a few water layers in each interlayer. The interlayer space expanded by 0.10 nm upon caffeine uptake (intercalation) and saturated even in the presence of excess caffeine. Time-cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The basal spacing was linearly increased with the amount of adsorbed caffeine (d 001 = 0.14W + 1.52 nm, r 2 = 0.95), as previously reported for caffeine uptake on BA−KF. 48 The adsorbed amounts of caffeine (mmol/g) are stated in Figure 2b. Clearly, interlayer expansion was triggered by the intercalation of caffeine molecules.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The basal spacing was linearly increased with the amount of adsorbed caffeine (d 001 = 0.14W + 1.52 nm, r 2 = 0.95), as previously reported for caffeine uptake on BA−KF. 48 The adsorbed amounts of caffeine (mmol/g) are stated in Figure 2b. Clearly, interlayer expansion was triggered by the intercalation of caffeine molecules.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Assuming that the change in basal spacing involves both rapid (d rapid ) and slow (d slow ) components, 48 we fitted the time-course plots obtained at different initial concentrations to first-order relaxation kinetics (see Figure 4b). Specifically, the time-course profile eq 4-1 was fitted by a double exponential (DE), described as the weighted sum of two first-order equations describing the kinetics of d rapid and d slow (eqs 4-2 and 4-3, respectively):…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The water molecules are located in the zeolitic cavities of the interlayer region 21 . In the past, several authors have reported that caffeine can be successfully intercalated in lamellar solids reaching interesting goals [22][23][24][25][26][27]28 . Herein we report the first intercalation of CAF on ZrP, obtaining an intercalation product that has been successfully used to prepare a stable emulsion.…”
Section: Figure 1: Chemical Structure Of Caffeinementioning
confidence: 99%
“…The adsorptive properties of layered inorganic solids (interlayer space of the nanosheets) are of our currently research interests . The smectite group of layered clay minerals is, in particular, established host materials as molecular recognizable adsorbents by modifying the interlayer space (e. g., pillaring, organophilic modification), of the silicate layers (1 nm‐thickness in each) owing to their swelling and cation‐exchange abilities. Controlled morphology (particle size distribution and shape) is also a viewpoint to be focused on enhancing material's applicability.…”
Section: Introductionmentioning
confidence: 99%